Polarization-diffusion versus sustainable development and economic concepts promoted by the Civic Platform and Law and Justice - Stelmach, Andrzej; Chrobak, Piotr; Kurek, Adam (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2024)
The article analyzes key issues related to the polarization-diffusion model of social and economic development. It compares this model with the concept of sustainable development and examines their impact on the economic development of the country. The authors aimed to determine whether, in such a highly polarized political environment, it is possible to create a common cross-party, long-term economic development strategy. The goal of that strategy is to remain stable despite changes in political leadership. However, this seems challenging due to the fact that supporters of the polarization-diffusion system dominate in larger centers of western Poland and large cities, much like the voters of Civic Platform (PO RP). In contrast, opponents of the system dominate smaller towns and rural areas, aligning with supporters of Law and Justice. Given that these two major political parties advocate for opposing models of economic development, it appears unlikely that Civic Platform and Law and Justice will agree on a unified plan for state economic development across party lines. W artykule przeanalizowano najważniejsze kwestie związane z funkcjonowaniem systemu polaryzacyjno-dyfuzyjnego rozwoju społecznego i ekonomicznego w zestawieniu z koncepcją systemu zrównoważonego rozwoju oraz ich wpływ na rozwój gospodarczy państwa. Autorzy starali się znaleźć odpowiedź, czy na tak silnie spolaryzowanej scenie politycznej, można wypracować wspólną ponadpartyjną wieloletnią koncepcję rozwoju gospodarczego państwa, tak aby jej nie zmieniać wraz ze zmieniającymi się partiami sprawującymi władzę. Jednak ze względu na fakt, że zwolennicy systemu polaryzacyjno-dyfuzyjnego dominują w większych ośrodkach zachodniej Polski i wielkich miastach, podobnie jak wyborcy PO RP, a przeciwnicy wspomnianego systemu dominują w mniejszych miejscowościach i wsiach, czyli tak jak zwolennicy PiS, to w tej sytuacji wydaje się, że skoro elektoraty dwóch największych partii opowiadają się za różnymi oraz przeciwstawnymi modelami rozwoju gospodarczego państwa, trudno będzie oczekiwać, że zarówno Platforma, jak i PiS wypracują wspólny plan rozwoju gospodarczego państwa ponad partyjnymi podziałami.
Polaryzacyjno-dyfuzyjny system funkcjonowania państwa kontra zrównoważony rozwój a koncepcje gospodarcze Platformy Obywatelskiej oraz Prawa i Sprawiedliwości
Keywords: polarization-diffusion model; sustainable development; regional policy; Civic Platform; Law and Justice; model polaryzacyjno-dyfuzyjny; zrównoważony rozwój; polityka regionalna; Platforma Obywatelska; Prawo i Sprawiedliwość